Fanaticism and Its Impact on Mental Health: A Literature Synthesis Study in the Indonesian Context - Dian Fitria; Dhea Natashia; Jehan Puspasari (Optimal Nursing Journal, 2024)
The enthusiastic engagement of Indonesian society in democratic processes, particularly during presidential elections and representation selections, highlights a notable manifestation of fanaticism across various domains. This phenomenon, while not novel, often generates conflicts, tensions, and mental health challenges. Methods: This article provides an overview of the impact of fanaticism on mental health using a literature synthesis approach. A systematic search was conducted across three reputable databases: Google Scholar, PubMed, and Taylor and Francis Online. The search strategy included keywords such as "fanaticism," "mental health," "Indonesia," and related terms. Articles were selected based on their relevance to the topic and inclusion of empirical evidence or theoretical insights. After the initial search, articles were screened based on their titles and abstracts to identify relevant literature. Full-text articles were then retrieved and thoroughly examined to assess their suitability for inclusion in the synthesis. Articles that met the inclusion criteria were further analyzed. Data synthesis involved identifying common themes, patterns, and trends across the selected articles, facilitating a comprehensive understanding of the impact of fanaticism on mental health in the Indonesian context.Results: Findings depict fanaticism as more than mere admiration, evolving into a profound commitment that shapes individuals' self-perception. This internalization fosters a belief in absolute righteousness, intolerance towards dissenting viewpoints, and alienation of those outside the established narrative. Consequently, individuals may experience psychological repercussions such as anxiety, anger, and frustration. Moreover, fanaticism can culminate in severe outcomes including antisocial behavior and self-harm. Discussion: Exploring the connection between fanaticism and mental health underscores the importance of understanding and addressing this complex phenomenon in society. By acknowledging the psychological impacts of fanaticism, interventions and support mechanisms can be developed to mitigate its adverse effects and promote societal well-being